Liquidity and Business Performance : A Study of Selected Indian Banks - Budhedeo, Shradha H.; Pandya, Neha; Pandya, Neha (Indian Journal of Finance, 2020)
Banks across the globe are facing liquidity issues. Sound liquidity management can reduce the probability of serious problems. Ideally, a bank needs to maintain enough high-quality liquid assets to meet its liquidity needs to withstand all kinds of possible stress situations. During the early phase of the 2008 financial crisis, many banks did not manage their liquidity prudently. These banks experienced major difficulties despite adequate levels of capital reserves. The Indian banks responded to the crisis by adopting cautious liquidity management policies. Alternatively, higher liquidity could work unfavorably for banks and mean smaller business. In this context, the present study attempted to understand the liquidity management by Indian banks and its impact on their business. The study focused upon selected large public and private sector banks so as to analyze and compare the liquidity and business performance of banks before the financial crisis (2001-02 – 2007-08) and after the crisis (2008-09 – 2018-19). The results revealed that Indian banks preferred higher liquidity in the post-crisis phase. At the same time, they cautiously managed to grow their business, albeit at a slower pace.